10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: While pasteurized donor human milk (PDHM) is increasingly available to hospitalized infants, PDHM use in the outpatient setting has limited precedent. This research describes one mother's experience with acquiring and using PDHM in the outpatient setting for an infant with complex care needs.Case Selection and Methods:We reviewed a list of infants receiving PDHM in the outpatient setting from a regional milk bank and sub-selected potential infant cases to profile based on recency of PDHM receipt and diversity of circumstances surrounding PDHM use and need. The mother of one infant responded to our request for an interview. A telephone interview was conducted with the mother, and the infant's medical records were reviewed. CASE PRESENTATION: Following birth, the selected infant was diagnosed with genetic anomalies associated with a high palate, small jaw, feeding intolerance, and respiratory dysfunction. Although the mother produced enough milk to meet her infant's needs during hospitalization, her supply declined rapidly following the infant's transfer to a pediatric step-down facility and her return to work. Trials of commercial infant formula were not tolerated by the infant, mainly due to the aforementioned diagnosis. After learning about PDHM from her own research, the mother engaged in 4 months of letter writing and telephone calls with staff at the milk bank, her employment-based health insurer, and Medicaid. PDHM was eventually covered by Medicaid for 10 months, which included 3 coverage renewals. The infant progressed well medically and developmentally on an all-human milk diet, including PDHM and direct breastfeeding, until she was 20 months old, at which point they began to self-wean. CONCLUSION: This case illustrates that PDHM may still be medically necessary in the outpatient setting and that pediatric care coordination/case management and discharge planning should include assistance with outpatient PDHM cost coverage.